2009
DOI: 10.3184/095422909x12548513972085
|View full text |Cite
|
Sign up to set email alerts
|

On the formation of calcium(II) taurocholate aggregate species in aqueous solution

Abstract: The influence of the presence of calcium(II) ions in solutions containing sodium and taurocholate ions at 25 degrees C and in 0.5 mol dm(-3) N(CH(3))(4)Cl as the constant ionic medium was studied. The composition and existence range of aggregates formed by taurocholate sodium and calcium(II) were investigated by means of two different procedures. First, the increasing calcium oxalate solubility due to the presence of taurocholate ions was studied as a function of the taurocholate, sodium and hydrogen ions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Previous , studies carried out on solutions containing calcium(II) and taurocholate and taurodeoxycholate showed that no precipitate is formed in a wide range of concentration, but only aggregates with different compositions.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous , studies carried out on solutions containing calcium(II) and taurocholate and taurodeoxycholate showed that no precipitate is formed in a wide range of concentration, but only aggregates with different compositions.…”
Section: Resultsmentioning
confidence: 97%
“…The formation of micellar aggregates of calcium(II), taurocholate (TC) and taurodeoxycholate (TDC), was investigated in previous papers. , It was found that both these salts are soluble and the composition of premicellar and micellar aggregates was found.…”
Section: Introductionmentioning
confidence: 99%
“…As many other papers (Bottari and Festa, 2002, 2003, 2004Antonilli et al, 2009;Bonincontro et al, 2008;Bottari et al, 1999) on this subject demonstrated, the behaviour of dihydroxycholanic salts is different with respect to trihydroxycholanic salts, such as cholic, glycocholic and taurocholic, which form aggregates with lower aggregation number and even, having as building block a dimer or, for the bigger species, an octamer.…”
Section: Discussionmentioning
confidence: 93%
“…Then after considering the other variables can represent a good approximate solution. This procedure, as applied to the treatment of the experimental data, will be explained briefly because it is similar to that applied in the case of taurocholate (Antonilli et al, 2009).…”
Section: Solubility Resultsmentioning
confidence: 99%
See 1 more Smart Citation